The concept of a religious house and its importance to the religious life - SZEWCZUL, BOŻENA (Prawo Kanoniczne, 2013)
Religious life and the practice of community life that is related to it entails religious residence in the religious house. The understanding (comprehension) of the religious house even by the religious themselves is very often limited to the building in which the religious reside. The task of the author, based on her conducted research, was to formulate the correct definition of the religious house resulting from Canons 608 and 609 CIC 1983, and to show its relevance for a religious in her/his pursuit of holiness. It turns out that in addition to building the concept of a religious house includes the community of religious living under the jurisdiction of a superior as well as the entirety of life of that community with the particular emphasis on its spiritual dimension centered around the religious house chapel which is the necessary part of the house. Hence it is important that at the time of the establishment of a religious house were taken into account all of its constituent elements which are mentioned in Canons 608 and 609 CIC 1983.